Багатокритеріальний аналіз функціонування інтернет-провайдерів в Україні - Пастушенко, І. Ю. (ХНУРЕ, 2023)
The purpose of the work is the analyze the technology of building Internet service providers, study mechanisms for ensuring the quality of service, and develop recommendations for improving the quality of service. The main characteristics of the quality of service of Internet service providers are determined and the criteria are given, according to which it is possible to evaluate and choose the quality of service. A multi-criteria analysis was carried out using a heuristic procedure and a mechanism for ensuring the necessary quality of service for each user when choosing an Internet service provider was proposed.
Keywords: інтернет-провайдер; багатокритеріальний аналіз